The Insertion allele of angiotensin converting enzyme increases the risk for coronary artery ectasia - Tekedereli, Ibrahim; Kara, Murat; Dagli, Necati; Gurevin, Mehmet Sait; Kobat, Mehmet Ali (Drunpp-Sarajevo, 2012)
Coronary artery ectasia(CAE) is characterized by dilation of the coronary arteries, exceeding the 1.5-fold of normal adjacent segment in coronary angiography. A common polymorphism in the angiotensin converting enzyme (ACE) gene is insertion/deletion (I/D) polymorphism. The presence of D allele has been shown to be associated with higher blood ACE concentrations. One hundred CAE patients and the 100 healthy controls were enrolled in the study. The frequencies of DD, ID and II genotypes were 42, 48 and 10% for CAE patients, 65, 33 and 2% for healthy controls, respectively (p=0.0014). The allele frequencies for D and I allele were 0.815 and 0.185 for the control group and 0.660 and 0.340 for the patient group (p=0.0004). In conclusion, our data suggest that the I allele which represents lower ACE levels leads to a decrease in vascular tone and increase in the susceptibility to CAE.
Keywords: Coronary artery ectasia; Angiotensin converting enzyme; Polymorphism